The Evolution of 'Ecological Release' into the 21st Century. (March 2021) - Herrmann, Nicholas C.; Stroud, James T.; Losos, Jonathan B.
Abstract : Ecological release, originally conceived as niche expansion following a reduction in interspecific competition, may prompt invasion success, morphological evolution, speciation, and other ecological and evolutionary outcomes. However, the concept has not been recently reviewed. Here, we trace the study of 'ecological release' from its inception through the present day and find that current definitions are broad and highly varied. Viewing this development as a potential impediment to clear communication and hypothesis testing, we suggest a consensus definition for ecological release: niche expansions and shifts when a constraining interspecific interaction is reduced or removed. In rationalizing this definition, we highlight the various ways ecological release can unfold and address its potential evolutionary consequences. Highlights: Ecological release, as both a concept and a term, has not been recently reviewed. Ecological release was originally conceived as niche expansion following a reduction in interspecific competition. Modern definitions are broad and varied – they encompass underlying mechanisms other than competition and accept signals other than niche expansion as potential evidence that ecological release has occurred. Niche changes during ecological release may prompt consequent morphological evolution and/or adaptive speciation, but these evolutionary outcomes themselves do not constitute ecological release. Hypotheses about evolutionary outcomes may be improved by explicitly considering how population- and individual-level niche dynamics can vary during ecological release.